ORBITER: a Lightweight Framework for Automatic Deployment of Big Data Applications on Serverless Architectures - Loureiro, João; Monteiro, José Maria; Bedo, Marcos; de Oliveira, Daniel (Journal of Information and Data Management, 2023)
The Serverless Computing paradigm has become a reality, with various public cloud environments offering serverless infrastructure and functionalities for general use. One of the main advantages of deploying applications in serverless architectures is that developers can focus on implementing the application and business logic while avoiding the complexities of deployment. However, despite these advantages, there are still challenges to consider, such as the delay in building the architecture of the distributed application. In this article, we introduce a lightweight framework designed for deploying big data applications in a serverless architecture, specifically following the Function-as-a-Service (FaaS) model. The proposed framework uses open-source tools and was thoroughly evaluated through the implementation of two practical applications for Crime Hot Spot Analysis and Rainfall Analysis in the Microsoft Azure cloud. The results of our evaluation demonstrated the potential of the proposed framework in streamlining the deployment process with acceptable overhead.